Multi-omics reveal the neuroprotective mechanisms of Xinshubao tablet against scopolamine-induced cognitive dysfunction in mice - Yang, Zhe; Zhang, Feng-Rong; Ren, Lu; Bai, Jia-Ming; Wang, Shi-Cong; Li, Xian-Yu; Yang, Hong-Jun; Xiao, Hong-He (Frontiers in Pharmacology, 2025)
IntroductionAlzheimer’s disease (AD) is a progressive neurodegenerative disorder with limited treatments. Xinshubao tablet (XSB), a traditional Chinese medicine, contains several bioactive compounds with notable neuroprotective effects. Our previous studies have demonstrated that XSB can alleviate cognitive deficits in vascular dementia (VaD) models, suggesting its potential as a therapeutic candidate for AD.MethodsIn this study, scopolamine-induced AD-like mice were orally administered with varying doses of XSB (0.13 g/kg, 0.26 g/kg and 0.52 g/kg) for 28 days. Behavior tests, H&E, Nissl, immunofluorescence staining, and Western blot assays were performed to evaluate the neuroprotection of XSB on AD-like mice. Then, fecal 16S rDNA sequencing, serum metabolomics, and hippocampal mRNA sequencing (mRNA-seq) analysis were performed to investigate the underlying mechanisms.Results and discussionThe results revealed that oral administration of XSB improved cognitive function, mitigated neuropathological damage, and alleviated dysfunction in the cholinergic system in AD-like mice. XSB treatment also enhanced gut microbiota diversity, increased the abundance of Enterococcus, Actinobacteriota, Coriobacteriales, and Eggerthellaceae, but reduced the abundance of Helicobacter rodentium and Lachnospiraceae. Integrating mRNA-seq and metabolomics data highlighted key regulatory pathways including the biosynthesis of unsaturated fatty acids, tyrosine metabolism, and glycerophospholipid metabolism. Furthermore, XSB treatment reduced the expression of TNF-α, IL-1β, MPO, enhanced SOD, GSH activities, reduced malondialdehyde (MDA) levels, upregulated the expression of BDNF, SYN, PSD95, and improved synaptic density. Transformation of XSB derived fecal microbiota (XSB-FM) effectively alleviated cognitive dysfunction and intestinal barrier injures. In conclusion, XSB may exert its neuroprotective effects via the microbiota-metabolite-brain axis, thereby improving neuroinflammation, neurotransmission, and synaptic integrity. These findings support the potential of XSB as a multifactorial therapeutic strategy for cognitive deficits in AD.